Thickness-dependent photoelectrochemical properties of a semitransparent Co3O4 photocathode - Patel, Malkeshkumar; Kim, Joondong (Beilstein Journal of Nanotechnology, 2018)
Co3O4 has been widely studied as a catalyst when coupled with a photoactive material during hydrogen production using water splitting. Here, we demonstrate a photoactive spinel Co3O4 electrode grown by the Kirkendall diffusion thermal oxidation of Co nanoparticles. The thickness-dependent structural, physical, optical, and electrical properties of Co3O4 samples are comprehensively studied. Our analysis shows that two bandgaps of 1.5 eV and 2.1 eV coexist with p-type conductivity in porous and semitransparent Co3O4 samples, which exhibit light-induced photocurrent in photoelectrochemical cells (PEC) containing the alkaline electrolyte. The thickness-dependent properties of Co3O4 related to its use as a working electrode in PEC cells are extensively studied and show potential for the application in water oxidation and reduction processes. To demonstrate the stability, an alkaline cell was composed for the water splitting system by using two Co3O4 photoelectrodes. The oxygen gas generation rate was obtained to be 7.17 mL·h−1 cm−1. Meanwhile, hydrogen gas generation rate was almost twice of 14.35 mL·h−1·cm−1 indicating the stoichiometric ratio of 1:2. We propose that a semitransparent Co3O4 photoactive electrode is a prospective candidate for use in PEC cells via heterojunctions for hydrogen generation.
Keywords: cobalt(II,III) oxide (Co3O4); photocathode; photoelectrochemical cells; semitransparent; thickness-dependent properties